Rise of Quad as a ‘Premier Regional Grouping’ - Vibhanshu Shekhar (Journal Of Global Strategic Studies, 2022)
The rise of the Biden Administration in the United States has coincided with the rise of Quad as a ‘premier regional grouping’ in the Indo-Pacific region with a robust agenda of cooperation that spans across strategic, economic, technological, environmental and developmental areas. The Quad’s ambitious agenda underpins the member-states’ deliberate effort to align its two foundational bases – balancing and normative – in the grouping’s outlook. The new Quad aims at achieving three-fold objectives – limiting China’s growing influence and assertive behaviour, augmenting new technological capacity of its member-states and projecting the grouping as a provider of regional good. However, the Quad continues to face various challenges, which relate to both the intent and functional capacity of the member-states and limit the grouping’s effectiveness in achieving its vastly ambitious agenda. The success of the Quad as an informal regional grouping will depend on the member-states’ willingness to overcome differences and navigate across diverse strategic priorities to chart a shared journey.